Improving cardiovascular health and quality of life in people with severe mental illness: study protocol for a randomised controlled trial - Battersby, Malcolm (Trials, 2018)
BACKGROUND: The estimated 300,000 adults in Australia with severe mental illness (SMI) have markedly reduced life expectancy compared to the general population, mainly due to physical health comorbidities. Cardiovascular disease (CVD) is the commonest cause of early death and people with SMI have high rates of most modifiable risk factors, with associated quality of life (QoL) reduction. High blood pressure, smoking, dyslipidaemia, diabetes and obesity are major modifiable CVD risk factors. Poor delivery of recommended monitoring and risk reduction is a national and international problem. Therefore, effective preventive interventions to safeguard and support physical health are urgently needed in this population. METHODS: This trial used a rigorous process, including extensive piloting, to develop an intervention that delivers recommended physical health care to reduce CVD risk and improve QoL for people with SMI. Components of this intervention are integrated using the Flinders Program of chronic condition management (CCM) which is a comprehensive psychosocial care planning approach that places the patient at the centre of their care, and focuses on building their self-management capacity within a collaborative approach, therefore providing a recovery-oriented framework. The primary project aim is to evaluate the effectiveness and health economics of the CCM intervention. The main outcome measures examine CVD risk and quality of life. The second aim is to identify essential components, enablers and barriers at patient, clinical and organisational levels for national, sustained implementation of recommended physical health care delivery to people with SMI. Participants will be recruited from a community-based public psychiatric service. DISCUSSION: This study constitutes the first large-scale trial, worldwide, using the Flinders Program with this population. By combining a standardised yet flexible motivational process with a targeted set of evidence-based interventions, the chief aim is to reduce CVD risk by 20%. If achieved, this will be a ground-breaking outcome, and the program will be subsequently translated nationwide and abroad. The trial will be of great interest to people with mental illness, family carers, mental health services, governments and primary care providers because the Flinders Program can be delivered in diverse settings by any clinical discipline and supervised peers. TRIAL REGISTRATION: Australian and New Zealand Clinical Trials Registry, ACTRN12617000474358. Registered on 31 March 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2748-7) contains supplementary material, which is available to authorized users.